Peningkatan Hasil Belajar Lari melalui Penerapan Project Based Learning Siswa Kelas IV di Sekolah Dasar - Gaguk Iriana (Faculty of Education Universitas Negeri Malang, 2016)
Abstract: The Improvement of the Results of Run Learning through the Implementation of Project Based Learning Grade IV in Elementary School. The problems found in the process of learning indicates that students understand the material being taught. The purpose of this research was to prove whether the application of the model of Learning Project Based Learning can improve learning outcomes basic motion run on elementary school students. The study used is the class action Research (School Action Research). Data analyzed by looking at the percentage of the increase that occurred from cycle to cycle. The results showed the applicability of Project Based Learning can improve student learning outcomes.Abstrak: Peningkatan Hasil Belajar Lari melalui Penerapan Project Based Learning Siswa Kelas IV di Sekolah Dasar. Permasalahan yang ditemukan dalam proses pembelajaran menunjukkan bahwa siswa kurang memahami materi yang diajarkan. Tujuan penelitian ini untuk membuktikan apakah penerapan model pembelajaran project based learning dapat meningkatkan hasil belajar gerak dasar lari pada siswa Sekolah Dasar. Penelitian yang digunakan adalah penelitian tindakan kelas (classroom action research). Data dianalisis dengan melihat persentase peningkatan yang terjadi dari siklus ke siklus. Hasil penelitian menunjukkan penerapan project based learning dapat meningkatkan hasil belajar siswa.